The optimal timing of greenhouse gas emission abatement, individual rationality and intergenerational equity - Richard S. J. Tol (Fondazione Eni Enrico Mattei (FEEM), 1998)
This paper explores the relationship between rationality and equity in an intergenerational context of greenhouse gas emission reduction. It is shown that the least-cost trajectory to a constraint on cumulative emissions implies an upward-sloping emission reduction effort, in most cases, whether technological development is exogenous or endogenous (either investments in research, development and demonstration or learning-by-doing). The least-cost trajectory, however, also implies in most cases that generations in the further future face higher relative costs than do generations in the nearer future. Cost-effectiveness thus may well violate intergenerational equity and rationality of future decision makers. More equitable solutions would lead to a relative shift of abatement effort to the near future, although emission reduction would still be increasing over time. In all cases, technological development in the earlier decades is very important.
Keywords: Q25; Q40; 330; Climate change; Timing of emission abatement; Cost-effectiveness; Rationality; Equity; Immissionsschutz; Klimawandel; Kosten-Wirksamkeits-Analyse; Rationales Verhalten; Gerechtigkeit; Generationengerechtigkeit; Theorie